A Combination of Blood Pressure and Total Cholesterol Increases the Lifetime Risk of Coronary Heart Disease Mortality: EPOCH–JAPAN - Satoh, Michihiro (J Atheroscler Thromb, 2021)
Aim: Lifetime risk (LTR) indicates the absolute risk of disease during the remainder of an individual's lifetime. We aimed to assess the LTRs for coronary heart disease (CHD) mortality associated with blood pressure (BP) and total cholesterol levels in an Asian population using a meta-analysis of individual participant data because no previous studies have assessed this risk. Methods: We analyzed data from 105,432 Japanese participants in 13 cohorts. Apart from grade 1 and 2–3 hypertension groups, we defined “normal BP” as systolic/diastolic BP < 130/< 80 mmHg and “high BP” as 130–139/80–89 mmHg. The sex-specific LTR was estimated while considering the competing risk of death. Results: During the mean follow-up period of 15 years (1,553,735 person-years), 889 CHD deaths were recorded. The 10-year risk of CHD mortality at index age 35 years was ≤ 0.11%, but the corresponding LTR was ≥ 1.84%. The LTR of CHD at index age 35 years steeply increased with an increase in BP of participants with high total cholesterol levels [≥ 5.7 mmol/L (220 mg/dL)]. This risk was 7.73%/5.77% (95% confidence interval: 3.53%–10.28%/3.83%–7.25%) in men/women with grade 2–3 hypertension and high total cholesterol levels. In normal and high BP groups, the absolute differences in LTRs between the low and high total cholesterol groups were ≤ 0.25% in men and ≤ 0.40% in women. Conclusions: High total cholesterol levels contributed to an elevated LTR of CHD mortality in hypertensive individuals. These findings could help guide high-risk young individuals toward initiating lifestyle changes or treatments.